The handbook of polyhydroxyalkanoates. Volume 2, Kinetics, bioengineering, and industrial aspects - Koller, Martin (Researcher) (Boca Raton, FL : CRC Press, 2020)
This second volume of the "Handbook of Polyhydroxyalkanoates (PHA): Kinetics, Bioengineering and Industrial Aspects" focusses on thermodynamic and mathematical considerations of PHA biosynthesis, bioengineering aspects regarding bioreactor design and downstream processing for PHA recovery from microbial biomass. It covers microbial mixed culture processes and includes a strong industry-focused section with chapters on the economics of PHA production, industrial-scale PHA production from sucrose, next generation industrial biotechnology approaches for PHA production based on novel robust production strains, and holistic techno-economic and sustainability considerations on PHA manufacturing. Aimed at professionals and graduate students in Polymer (plastic) industry, wastewater treatment plants, food industry, biodiesel industry, this book Provides an insight into microbial thermodynamics to reveal the central domain governing in PHA formation, both aerobically and anaerobically. Includes systematic overview of mathematical modelling approaches, starting from low-structured and formal kinetic models until modern tools like metabolic models, cybernetic models and so forth Discusses challenges during scale up of PHA production processes and on development of non-sterile processes and contamination-resistant strains Presents a holistic picture of the current state of PHA research by mixed cultures Reviews the industry-related point of view about current and future trends in PHA production and processing
Chapter 1: An Introduction to the Thermodynamics Calculation of PHA Production in Microbes 1.1 Introduction 1.2 Introduction to Thermodynamics and its Application to PHA Synthesis 1.3 PHA Synthesis Under Aerobic Conditions 1.4 PHA Synthesis under Anaerobic Conditions 1.5 Conclusions and Outlook References Chapter 2: Mathematical Modelling for Advanced PHA Biosynthesis 2.1 Introduction 2.2 Kinetics of PHA Biosynthesis 2.3 Mathematical Modelling of PHA Biosynthesis 2.4 Metabolic Pathway and Flux Analysis Methods in Modelling of PHA Biosynthesis 2.5 Conclusions and Outlook References Chapter 3: Interconnection between PHA and Stress Robustness of Bacteria 3.1 Importance of Stress Robustness for Bacteria 3.2 PHA and stress induced by high temperature 3.3 Protective Functions of PHA Against Low Temperature and Freezing 3.4 Osmoprotective Function of PHA Granules 3.5 Protective Function of PHA Against Radiation 3.6 Oxidative Stress and PHA 3.7 Stress Induced by Heavy Metals and other Xenobiotics and PHA Metabolism 3.8 Conclusions and Outlook References Chapter 4: Linking Salinity to Microbial Biopolyesters Biosynthesis: Polyhydroxyalkanoate Production by Haloarchaea and Halophilic Eubacteria 4.1 Introduction 4.2 Halophilic microbes producing PHA 4.3 PHA production by Halophilic Archaea ("Haloarchaea") 4.4 Gram-Negative Halophilic Eubacteria as PHA Producers 4.5 Gram-positive halophilic PHA producers 4.6 Conclusions and Outlook References Chapter 5: Role of Different Bioreactor Types and Feeding Regimes in Polyhydroxyalkanoates Production 5.1 Introduction 5.2 Process Optimization for PHA Production 5.3 Reactor Operating Strategies for PHA Production 5.4 Nutrient Feeding Regimes for PHA Production 5.5 Conclusions and Outlook References Chapter 6: Recovery of Polyhydroxyalkanoates from Microbial Biomass 6.1 Introduction 6.2 PHA Recovery Methods 6.3 Mechanical Methods 6.4 Biological Recovery Methods 6.5 Physical Purification Methods 6.6 Conclusions and Outlook References Chapter 7: Polyhydroxyalkanoates by Mixed Microbial Cultures: The Journey so Far and Challenges Ahead 7.1 The Journey so Far 7.2 Definition of MMCs 7.3 A Little Bit of History 7.4 What Do We Know about PHA by MMCs? 7.5 Presently Accepted Strategies 7.6. Microorganisms and Metabolism 7.7. Challenges Ahead 7.8. Conclusions and Outlook References Chapter 8: PHA Production by Microbial Mixed Cultures and Organic Waste of Urban Origin: Pilot Scale Evidences 8.1. Introduction 8.2. MMC-PHA Production in the Urban Biorefinery Model 8.3. Pilot Scale Studies for Urban Waste Conversion into PHA 8.4 Conclusions and Outlook References Chapter 9: Production Quality Control of Mixed Culture Poly(3-Hydroxbutyrate-co-3-Hydroxyvalerate) Blends Using Full-Scale Municipal Activated Sludge and Non-Chlorinated Solvent Extraction 9.1 Introduction 9.2 Materials and methods 9.3 Results and Discussion 9.4 Conclusions and Outlook References Chapter 10: Economics and Industrial Aspects of PHA Production 10.1 Introduction 10.2 A Brief History of PHA 10.3 Physical Properties 10.4 Cost and Economics References Chapter 11: Next Generation Industrial Biotechnology (NGIB) for PHA Production 11.1 Introduction 11.2. Chassis for NGIB 11.3. Production of PHA by Halophiles 11.4. Genetic Tools for Halophile Engineering 11.5. Engineering Halomonas spp. for PHA production 11.6. Morphology Engineering for Easy Separation 11.7. Conclusions and Outlook References Chapter 12: PHA Biosynthesis Starting from Sucrose and Materials from Sugar Industry 12.1. Introduction of Sucrose for PHA production 12.2. Use of Molasses for PHA Production 12.3. Bacterial strains for PHA production from sucrose 12.4. Setting up a biorefinery to produce PHA in Brazil 12.5. A new Biorefinery for PHA Production in Brazil 12.6. Conclusions and Outlook References Chapter 13: LCA, Sustainability and Techno-economic Studies for PHA Production 13.1 Introduction 13.2 Economic Analysis 13.3 Sustainability of PHA Production 13.4. Conclusions and Outlook References
OCLC-licensed vendor bibliographic record.
Keywords: Poly-beta-hydroxyalkanoates.; TECHNOLOGY / Engineering / Chemical & Biochemical